Effects of Patient and Surgery Characteristics on Persistent Postoperative Pain: A Mediation Analysis. Issue 11 (November 2021) - Mi, Xinlei; Zou, Baiming; Rashidi, Parisa; Baharloo, Raheleh; Fillingim, Roger B.; Wallace, Margaret R.; Crispen, Paul L.; Parvataneni, Hari K.; Prieto, Hernan A.; Gray, Chancellor F.; Machuca, Tiago N.; Hughes, Steven J.; et al.
Abstract : Objective: Acute postoperative pain intensity is associated with persistent postsurgical pain (PPP) risk. However, it remains unclear whether acute postoperative pain intensity mediates the relationship between clinical factors and persistent pain. Materials and Methods: Participants from a mixed surgical population completed the Brief Pain Inventory and Pain Catastrophizing Scale before surgery, and the Brief Pain Inventory daily after surgery for 7 days and at 30 and 90 days after surgery. We considered mediation models using the mean of the worst pain intensities collected daily on each of postoperative days (PODs) 1 to 7 against outcomes of worst pain intensity at the surgical site endpoints reflecting PPP (POD 90) and subacute pain (POD 30). Results: The analyzed cohort included 284 participants for the POD 90 outcome. For every unit increase of maximum acute postoperative pain intensity through PODs 1 to 7, there was a statistically significant increase of mean POD 90 pain intensity by 0.287 after controlling for confounding effects. The effects of female versus male sex ( m =0.212, P =0.034), pancreatic/biliary versus colorectal surgery ( m =0.459, P =0.012), thoracic cardiovascular versus colorectal surgery (m =0.31, P =0.038), every minute increase of anesthesia time ( m =0.001, P =0.038), every unit increase of preoperative average pain score ( m =0.012, P =0.015), and every unit increase of catastrophizing ( m =0.044, P =0.042) on POD 90 pain intensity were mediated through acute PODs 1 to 7 postoperative pain intensity. Discussion: Our results suggest the mediating relationship of acute postoperative pain on PPP may be predicated on select patient and surgical factors.